Mean business : how I save bad companies and make good companies great - Dunlap, Albert J.; Andelman, Bob. (New York : Simon & Schuster, 1997)
Al Dunlap, who transformed the once-ailing Scott Paper into a Wall Street success story, shares has battle-tested strategies for revitalizing sluggish companies in Mean Business. Here is the inside story of Dunlap's quest to make Scott once again a world-class competitor. Along the way, Dunlap provides invaluable, must-read lessons for everyone struggling to meet the tough, competitive challenges of today's business world.
Includes index.
Keywords: Corporate turnarounds; Corporate turnarounds -- United States -- Case studies